2018
DOI: 10.3354/meps12660
|View full text |Cite
|
Sign up to set email alerts
|

Traits structure copepod niches in the North Atlantic and Southern Ocean

Abstract: Realised niches describe the environmental and biotic conditions that a species occupies. Among marine zooplankton, species traits, including body size, dietary mode (herbivore, omnivore, or carnivore), and diapause strategy are expected to influence the realised niche of a species. To date, realised niches are known for only a small number of copepod species. Here we quantify the realised niches of 88 copepod species measured by the Continuous Plankton Recorder (CPR) in the North Atlantic and Southern Ocean u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 97 publications
4
37
0
Order By: Relevance
“…This is highlighted by a preference for warmer temperatures within a rather narrow temperature range for C. helgolandicus and a broader temperature range with a preference for colder temperatures for C. finmarchicus. The derived thermal niches support previous observational studies and reviews demonstrating peak abundances of C. helgolandicus and C. finmarchicus at temperatures ≥ 13 C and < 10 C, respectively (Bonnet et al 2005;Helaouët and Beaugrand 2007;Jónasdóttir and Koski 2011;Melle et al 2014;McGinty et al 2018) and corresponds well to available meta-analysis across zooplankton taxa showing a general concave relationship with temperature (Forster et al 2011). The broader temperature range of C. finmarchicus allows it to tolerate a larger range of environments and consequently occupy a considerably larger distribution area, as evidenced by its widespread biogeography across the North Atlantic (Helaouët and Beaugrand 2007;Melle et al 2014).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is highlighted by a preference for warmer temperatures within a rather narrow temperature range for C. helgolandicus and a broader temperature range with a preference for colder temperatures for C. finmarchicus. The derived thermal niches support previous observational studies and reviews demonstrating peak abundances of C. helgolandicus and C. finmarchicus at temperatures ≥ 13 C and < 10 C, respectively (Bonnet et al 2005;Helaouët and Beaugrand 2007;Jónasdóttir and Koski 2011;Melle et al 2014;McGinty et al 2018) and corresponds well to available meta-analysis across zooplankton taxa showing a general concave relationship with temperature (Forster et al 2011). The broader temperature range of C. finmarchicus allows it to tolerate a larger range of environments and consequently occupy a considerably larger distribution area, as evidenced by its widespread biogeography across the North Atlantic (Helaouët and Beaugrand 2007;Melle et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The marine copepods Calanus finmarchicus, Calanus helgolandicus, Oithona atlantica, and Oithona similis represent two pairs of widespread and ecologically important zooplankton species in the North Atlantic. Despite their high abundances, the Oithona species are largely understudied (Gallienne and Robins 2001) and often excluded from comparative studies (McGinty et al 2018), primarily due to undersampling by most standard zooplankton sampling methods. In contrast, the Calanus species are very well studied and have attracted considerable attention in the literature (Bonnet et al 2005;Helaouët and Beaugrand 2007;Beaugrand and Helaouët 2008;Jónasdóttir and Koski 2011;Melle et al 2014).…”
mentioning
confidence: 99%
“…We are showing only one such configuration here because empirical modelling is not the focus of this review; the results shown represent the best of a series of MaxEnt configurations tested. While use of MaxEnt has become widespread for mapping biogeographies of species, it has only recently been applied to map the biogeography of a trait (McGinty, Barton, Record, Finkel, & Irwin, accepted).…”
Section: Methodsmentioning
confidence: 99%
“…copepods, is driven primarily by water depth and by sea ice dynamics (Hopkins & Torres, ); these environmental drivers affect overall copepod distribution in the water column as well as the ability of species to reproduce and develop (Makabe et al, ). Temperature is another factor expected to contribute to copepod niches, while dietary modes are related to chl a and wind stress (McGinty et al, ). In the Weddell Sea, copepod observations have primarily been collected in January and February, although data exist for all other months, including samples analyzed by gender and development stages (Cornils et al, ).…”
Section: Biology Ii: Food Web Of the Wgmentioning
confidence: 99%